Comparing estimated protein excretion rate and spot urinary protein-creatinine ratio in assessing urinary protein excretion in patients with kidney disease in China: a single center study - Jia, Yu; Zhao, Lingling; Wang, Fang; Shang, Jin; Zhao, Zhanzheng (Frontiers in Medicine, 2025)
ObjectivesThis study aimed to analyze the potential of the estimated protein excretion rate (ePER) as a substitute for the spot urinary protein-creatinine ratio (uPCR) in clinical reports for accurately assessing urinary protein excretion in China.MethodsWe included 1721 patients in the study and compared the differences in levels, correlation, bias, methodological evaluation between uPCR, ePER, and 24-h urinary protein.ResultsSignificant differences (Z = −17.568, p < 0.001) were found between uPCR and 24-h urine protein levels in all cases. However, no statistically significant difference (Z = −0.652, p = 0.514) was found between ePER and 24-h urine protein. The bias analysis revealed that the negative bias rate between ePER and 24-h urine protein was −4.33%, significantly lower compared to uPCR (−30.88%). Incorporating ePER significantly boosted its sensitivity to 91.3% in this cohort. Furthermore, ePER demonstrated a higher correlation (r = 0.74, p < 0.001) and kappa consistency (κ = 0.802, p = 0.015) with 24-h urinary protein compared to uPCR (r = 0.71, p < 0.001; κ = 0.737, p = 0.016). However, in the >65 age group, those with estimated glomerular filtration rate (eGFR) < 30 mL/min/1.73m2 group and spot urinary creatinine <500 mg/L exhibited a higher ePER bias compared to uPCR.ConclusionThese findings highlight the potential of ePER as a valuable tool for accurately assessing urinary protein excretion. Nonetheless, its limitations should be considered, especially in specific patient populations.